Pengaruh E-WOM terhadap Minat Berkunjung Dimediasi oleh Citra Destinasi pada Objek Wisata Bukit Gandrung Tanggulasi Kediri - Fitria, Novy Wahyuning; Mas, Nasharuddin; H, Dharmayanti Pri. (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The growth of digital technology has made E-WOM serves as one of the primary approaches used to market and promote tourist attractions. This study investigates the relationship between Electronic Word of Mouth (E-WOM) and tourists' intention to visit, as well as the mediating role of image goals in this relationship, with a specific focus on Bukit Gandrung Tanggulasi Kediri. Using the Partial Least Squares–Structural Equation Modelling (PLS-SEM) technique and taking a quantitative approach. The destination image's mediating function in this relationship, data were gathered from 102 respondents—comprising tourists and potential tourists who obtained information via social media platforms. The findings reveal a significant and positive E-WOM's impact on travellers’ intentions to visit. While E-WOM does not have a significant influence on destination image, destination image itself significantly affects tourist visit intention and acts as a mediating factor in the association between the intention of tourists to visit and E-WOM. These findings indicate that E-WOM messages can indirectly increase tourist interest by forming a positive perception of the destination image. From a practical perspective, this study recommends that destination managers strengthen the tourist experience through reviews and attractive visual content to build a good image and increase tourist interest.